Analisis Penerapan Aplikasi SNR (Sinar) Simpan Pinjam Di LPD Desa Adat Guwang - I Kadek Aditya Permana; I Putu Fery Karyada; Rai Dwi Andayani W (UNHI Press, 2023)
In serving customers, especially in terms of collecting customer daily savings funds, LPD Guwang implements a pick-up-ball system. In the process of collecting customer savings funds, LPD Guwang uses the SNR Savings and Loans application. The purpose of this study was to determine the application of the SNR Savings and Loans application at LPD Guwang which was studied based on the dimensions of the quality of the accounting information system. This research is a qualitative research, with data collection techniques in the form of observation, interviews and documentation. The results showed that: the application of the SNR Savings and Loans application was in accordance with (good) dimensions of integration; the SNR Savings and Loan application used in LPD Guwang is in accordance with (good) flexibility dimensions; the application of the SNR Savings and Loans application is quite good when viewed from the reliability dimension.